FRI0156 Pharmacokinetics of ABT-122, A Dual TNF- and IL-17A-Targeted DVD-IG™, After Single Dosing in Healthy Volunteers and Multiple Dosing in Subjects with Rheumatoid Arthritis. (9th June 2015) - Ahmed, G.F.; Goss, S.; Jiang, P.; Mansikka, H.; Padley, R.J.; Othman, A.A.
Abstract : Background: ABT-122 is a novel dual-variable domain immunoglobulin that specifically neutralizes both TNF alpha and interleukin-17A, with the dual neutralization aimed to achieve greater clinical response in immune-mediated inflammatory diseases than blocking either cytokine alone. Objectives: This work characterized the pharmacokinetics of ABT-122 after single [Intravenous (IV), subcutaneous (SC)] ascending doses in healthy volunteers or multiple SC ascending doses in subjects with rheumatoid arthritis (RA). Methods: ABT-122 pharmacokinetics was evaluated in three Phase 1 studies for up to 92 days. In Study 1, single- ascending IV (0.1, 0.3, 1, 3 and 10 mg/kg) and SC (0.3, 1 and 3 mg/kg) doses were evaluated in healthy volunteers. In Studies 2 and 3, multiple ascending SC doses (1 mg/kg biweekly, 0.5 to 3 mg/kg weekly for 8 weeks) were evaluated in subjects with RA on stable methotrexate (MTX) therapy. ABT-122 pharmacokinetic parameters were estimated using non-compartmental analyses. Results: Pharmacokinetic data were available from 48 healthy and 31 RA subjects with median body weights of 78 (range; 52 – 98) and 79 (range; 47 – 111) kg, respectively. ABT-122 pharmacokinetic profile showed multi-exponential disposition with more than dose-proportional exposure at the lower doses (0.1 – 1 mg/kg) and approximately dose-proportional exposure at doses >1 mg/kg. With SC dosing, ABT-122 absolute bioavailability was approximately 50% and maximum serum concentrations were reached 3 – 4 days after dosing. After the last dose, ABT-122 AUC accumulation ratio was 3.8 to 5.6 with steady-state appearing to be achieved by 5 weeks of SC dosing. ABT-122 Cmax to Ctrough ratio was 2.6 and 1.3 for biweekly and weekly dosing, respectively (corresponding effective half-life of 10 days with biweekly dosing and 18 days with weekly dosing). In most of the subjects, anti-drug antibodies detected had no detectable impact on pharmacokinetics, safety or tolerability profile of ABT-122. Conclusions: ABT-122 is characterized by a pharmacokinetic profile favorable for biweekly subcutaneous administration. The results from these three phase 1 studies supported advancing ABT-122 to Phase 2 testing in subjects with rheumatoid and psoriatic arthritis. Disclosure of Interest: G. Ahmed Shareholder of: AbbVie, Employee of: AbbVie, S. Goss Shareholder of: AbbVie, Employee of: AbbVie, P. Jiang Shareholder of: AbbVie, Employee of: AbbVie, H. Mansikka Shareholder of: AbbVie, Employee of: AbbVie, R. Padley Shareholder of: AbbVie, Employee of: AbbVie, A. Othman Shareholder of: AbbVie, Employee of: AbbVie